2012
DOI: 10.1080/07418825.2012.736526
|View full text |Cite
|
Sign up to set email alerts
|

Does Inmate Behavior Affect Post-Release Offending? Investigating the Misconduct-Recidivism Relationship among Youth and Adults

Abstract: Recent scholarship has highlighted the potential implications of in-prison experiences for prisoner reentry and, in particular, recidivism. Few penological or reentry studies, however, have examined the relationship between one experience that may be especially consequential, inmate misconduct, and recidivism. The goal of this study is to address this gap in the literature by employing a matching design that estimates the effect of inmate misconduct on reoffending, using data on a release cohort of Florida pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
96
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(105 citation statements)
references
References 73 publications
7
96
0
2
Order By: Relevance
“…An important finding was that aggressive misconduct was significantly associated with time to being charged with a violent offence following release into the community; this finding remained significant when controlling for the effect of risk for future violence, length of incarceration, ethnicity and age at time of release These results are consistent with previous research that has identified a significant relationship between misconduct and recidivism in adult offenders (Cochran et al, 2012;Heil et al, 2009) and lends support to the view that institutional aggression may be viewed as a proxy for future violence (French & Gendreau, 2006). Further, this result highlights that recorded aggressive behaviour in custody is uniquely associated with violent recidivism beyond formal risk assessment measurement (though it should be noted that institutional aggression is considered in reappraisals of violence risk in the VRS).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…An important finding was that aggressive misconduct was significantly associated with time to being charged with a violent offence following release into the community; this finding remained significant when controlling for the effect of risk for future violence, length of incarceration, ethnicity and age at time of release These results are consistent with previous research that has identified a significant relationship between misconduct and recidivism in adult offenders (Cochran et al, 2012;Heil et al, 2009) and lends support to the view that institutional aggression may be viewed as a proxy for future violence (French & Gendreau, 2006). Further, this result highlights that recorded aggressive behaviour in custody is uniquely associated with violent recidivism beyond formal risk assessment measurement (though it should be noted that institutional aggression is considered in reappraisals of violence risk in the VRS).…”
Section: Discussionsupporting
confidence: 88%
“…However, within this large body of research the focus is often on historical and preincarceration measures of offender behaviour, such as previous convictions, with less attention paid to the association between aggressive behaviour within the prison environment and violent recidivism following release (Trulson et al, 2011). Institutional behaviour may provide a useful source of information relating to an offender's level of risk that is not captured by variables measured pre-incarceration, given it is generally the most recent record of behaviour for offenders and such records are readily available to risk assessors (Cochran, Mears, Bales, & Stewart, 2012;Trulson et al, 2011). This is particularly important for offenders incarcerated for lengthy periods.…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of drug-using individuals may promote drug use in custody by providing opportunities for increased interaction between high-risk individuals. Drug use in prison also reportedly impairs rehabilitative goals (Baltieri, 2014) and may increase the likelihood that prisoners will be reincarcerated (Cochran, Mears, Bales, & Stewart, 2014). The aim of this study was to assess the relationship between prison drug use, duration of incarceration, and a range of covariates.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, aggressive incidents occurring in a psychiatric ward are shown to be associated with a decreased well-being of working staff, diminished professional behavior, an increased number of absences, and a higher workload (Di Martino, 2002;Estryn-Behar et al, 2008;Nijman, Palmstierna, Almvik, & Stolker, 2005;van der Helm, Boekee, Stams, & van der Laan, 2011). Furthermore, evidence exists for an association between inpatient aggression and a higher number of offenses after treatment (Cochran, Mears, Bales, & Stewart, 2014). The fact that inpatient aggression has such a severe negative impact on both staff and patients and shows possible negative consequences for society makes effective management and prevention of aggression key priorities in mental health settings (Kaltiala-Heino et al, 2007;Masters & Bellonci, 2002;Tremmery et al, 2012).…”
mentioning
confidence: 99%